Assessment of Expected Leadership Capacities in Higher Education Institutions: The Case of Jigdan College - Teshome, Samson Worku; H/Wold, Dawit Tefera; Birru, Yonas Tefera; Amedie, Wossenu Yimam (Darul Yasin Al Sys, 2025)
The primary purpose of this research is to assess the leadership capacities of leaders at JIGDAN College and the extent to which the current governance structure of the college supports these capacities. To this end, a mixed research approach and a convergent parallel design were employed. To achieve the objectives of the study, both primary and secondary data were collected from the leaders at the college and various documents. Primary data were gathered through questionnaires, while secondary data were obtained from documentary evidence. The primary data were analyzed using various descriptive statistical tools, including percentage, mean, and standard deviation, with SPSS version 20. The results regarding leadership capacities indicated that the highest leadership skills possessed by the leaders are time management and the effective use of technology. Conversely, the capacities in which they are most deficient include establishing external networks (relationships) at both national and international levels and the ability to inspire and persuade others. The governance structure is well organized, and relevant documentation is available within the organization. The leaders at the college demonstrate a clear understanding of change and change management. The college excels in its teaching-learning and community outreach services, surpassing its performance in research, innovation, and technology transfer missions typical of higher education institutions. A significant challenge facing the college leadership is the financial capacity required to implement the planned programs. To address these leadership challenges, it is recommended that the college management provide training to raise awareness in the areas where leadership is lacking and enhance its financial capacity.